Topical therapy of psoriasis vulgaris - a treatment pathway - Koerber, Andreas; Wilsmann-Theis, Dagmar; Augustin, Matthias; Von Kiedrowski, Ralph; Mrowietz, Ulrich; Rosenbach, Thomas; Meller, Stephan; Pinter, Andreas; Sticherling, Michael; Gerdes, Sascha (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
In daily practice topical treatment of psoriasis and its subtypes is of high importance. It is standard for the treatment of mild psoriasis and is used to support treatment of moderate-to-severe psoriasis. When optimizing psoriasis treatment not only the choice of suitable compounds, but also the formulation aspect matters. Developments in the latter field were not considered in the 2017 published update of the current S3-guideline on psoriasis. The presented pathway was prepared during a PsoNet speaker conference and confirmed by the national psoriasis care conference. It aims to illustrate current treatment options.
CRIS-Team WoS Importer:2019-05-09